2009
DOI: 10.1039/b907344b
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear absorption in a series of Donor–π–Acceptor cyanines with different conjugation lengths

Abstract: A detailed experimental and theoretical study of the linear and nonlinear absorption of a series of asymmetrical D-p-A cyanine dyes with the same trimethylindolin donor (D) and diethylaminocoumarin-dioxaborine acceptor (A) terminal groups and different conjugation lengths, is presented. Strong solvatochromic behavior affecting the fluorescence quantum yields, lifetimes, and the linear and nonlinear absorption properties is observed due to the presence of permanent ground state dipole moments. Detailed experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 38 publications
4
51
0
Order By: Relevance
“…As an illustration, the absorption spectra of dyes 4 derivatives of aminocoumarine synthesized by A.O. Gerasev et al [83][84][85][86][87] are presented in Figure 1b.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…As an illustration, the absorption spectra of dyes 4 derivatives of aminocoumarine synthesized by A.O. Gerasev et al [83][84][85][86][87] are presented in Figure 1b.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Gerasev et al [155][156][157] for the anionic polymethine dyes 4. Combined quantum-chemical and spectral studies of the dyes 4 [85][86][87] have shown that two lowest electron transitions are split transitions, involving two low positioned acceptor levels, in contrast to the cationic cyanine dyes where two lowest transitions are connected with two split donor levels.…”
Section: Introduction Of π π π π-Donor Substituents To Terminal Groupsmentioning
confidence: 95%
“…As a result, the excitation is efficiently localized, together with degeneracy of the two orthogonally polarized degenerate excited states strongly removed because of structure disorder and solvation, 26 leading to the decreased anisotropy value in the high-energy ICT side as shown in Figure 3. 13,66 Regarding chromophore 5, conjugation among the triphenylamine core and three branches through CC do exist, but it is not as strong as that in chromophore 4 because of the small twisting barrier of the CC bond. 10,58 Therefore, in chromophore 5, for low-energy ICT states, triphenylamine core is more active, charge is partially distributed overall molecule, and the CDD distribution at each branch agrees with C 3h symmetry Frenkel exciton model expressions (see Table S2e states, triphenylamine core is not that active, charge redistribution is partially restricted, and the CDD distribution is slightly different from the expressions of an ideal C 3h symmetry Frenkel exciton model.…”
mentioning
confidence: 99%
“…46,72 Since the selection rule is different for two-photon absorption from the one-photon absorption, 13,72 two-photon absorption is one of the most important nonlinear optical properties of organic charge-transfer molecules, which is strongly dependent on the molecular structure, such as electron donor and acceptor features, π-bridge group and length, geometric configuration, etc.…”
mentioning
confidence: 99%
“…This class of materials is extended to natural dyes which demonstrate a great interest in the field of NLO due to their high delocalized p-electron systems. Such functional materials are of special interest in the area of optical communications, optical storage, optical computing, harmonic generation, optical switching, and optical power limiting [4][5][6][7][8][9][10]. Several environmentally friendly and cost effective natural dyes including the family of chlorophyll [11], carotenoids [12] red Carmine, Chinese tea and betanin, Hibiscus sabdariffa as well as, recently, functionalized DNA [13][14][15][16][17][18] have been investigated.…”
Section: Introductionmentioning
confidence: 99%